2008
DOI: 10.1186/ar2540
|View full text |Cite
|
Sign up to set email alerts
|

Association of a single nucleotide polymorphism in growth differentiate factor 5 with congenital dysplasia of the hip: a case-control study

Abstract: Introduction Congenital dysplasia of the hip is an abnormal seating of the femoral head in the acetabulum, mainly caused by shallow acetabulum and lax joint capsule. Genetic factors play a considerable role in the pathogenesis of congenital dysplasia of the hip. The gene growth differentiate factor 5 (GDF5) has been implicated in skeletal development and joint morphogenesis in humans and mice. A functional single nucleotide polymorphism (SNP) in the 5'-untranslated region of GDF5 (rs143383) was reported to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 32 publications
6
64
0
1
Order By: Relevance
“…Our data have shown that polymorphism exist in the GDf-5 (BsiE1) gene in North Indian population. The frequency of T allele in our population (55%) was similar to that reported in Caucasians (59-63 %) (Rouault et al, 2010;Southam et al, 2007;Tsezou et al, 2008;Valdes and Spector, 2009) the oriental population carry relatively higher frequency (70-74%) of variant T allele (Shin et al, 2012;Cao et al, 2010;Dai et al, 2008;Miyamoto et al, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…Our data have shown that polymorphism exist in the GDf-5 (BsiE1) gene in North Indian population. The frequency of T allele in our population (55%) was similar to that reported in Caucasians (59-63 %) (Rouault et al, 2010;Southam et al, 2007;Tsezou et al, 2008;Valdes and Spector, 2009) the oriental population carry relatively higher frequency (70-74%) of variant T allele (Shin et al, 2012;Cao et al, 2010;Dai et al, 2008;Miyamoto et al, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…Despite our better understanding of the pathology and all current methods of screening, many young adults with dysplasia who require hip arthroplasty are not detected at birth [37] . In the future, genetic profiling may improve matters [38] . Physical examination [1,5] DDH is an evolving process, therefore the physical examination changes as the child grows older.…”
Section: Screening For Ddhmentioning
confidence: 99%
“…It is thought that female babies are at higher risk due to their susceptibility to the maternal hormone relaxin, which may contribute to ligamentous laxity in the hip joint (Maclennan and Maclennan, 1997). There is limited information on what genes may be responsible for the familial incidence of DDH, with most studies proposing an association between a genetic or chromosome variant and DDH being focussed on individual families or single ethnicities (Dai et al, 2008;Feldman et al, 2010;Feldman et al, 2012;Hao et al, 2014;Rouault et al, 2010;Tian et al, 2012), limiting their impact on the wider population. However, evidence that GDF-5 may be linked with DDH has been revealed for both Chinese Han (Dai et al, 2008) and western Brittany (Rouault et al, 2010) patient groups.…”
Section: Risk Factorsmentioning
confidence: 99%